2017
DOI: 10.1111/echo.13555
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe tricuspid regurgitation on accuracy of systolic pulmonary arterial pressure measured by Doppler echocardiography: Analysis in an unselected patient population

Abstract: Pulmonary arterial pressure is an important index in cardiovascular disorders, especially for pulmonary hypertension (PH). Doppler echocardiography (DE) is widely used as a noninvasive method to assess pulmonary arterial pressure. However, recent studies have found several hemodynamic factors that affect its accuracy in estimating systolic pulmonary arterial pressure (sPAP). But the effect of tricuspid regurgitation (TR) has not been investigated. Therefore, our study is aimed to determine whether the severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Finally, one of the advantages of the present study was that the time interval between echocardiography and RHC was smaller than the previous studies. 10,18,33) Although we performed echocardiography within 24 hours of RHC, they were within 48 hours 10) and 5 days, 18,33) respectively, in these previous studies. Study limitations: This study has several limitations.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, one of the advantages of the present study was that the time interval between echocardiography and RHC was smaller than the previous studies. 10,18,33) Although we performed echocardiography within 24 hours of RHC, they were within 48 hours 10) and 5 days, 18,33) respectively, in these previous studies. Study limitations: This study has several limitations.…”
Section: Discussionmentioning
confidence: 91%
“…Other investigators demonstrated a poor correlation in patients with certain medical conditions. [31][32][33] Fei, et al 33) indicated that the accuracy of the systolic PAP measured by DE was affected by severe TR and severe PH. In our study, we documented sPAP overestimation and underestimation in Table III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible reasons for this discrepancy are different reference intervals for TAPSE, different sample population size, different underlying etiology of PH, and possibly different clinical severity among dogs with severe PH. Moreover, severe TR can influence the Doppler estimation of pulmonary arterial pressure and is a significant confounding factor when applying TAPSE to assess RV function . As is known, TAPSE increases with TR severity irrespectively of RV function.…”
Section: Discussionmentioning
confidence: 99%